2013
DOI: 10.1245/s10434-013-3211-3
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Patterns and Prognostic Factors in Patients with Hepatocellular Carcinoma in Noncirrhotic Liver: A Multi-Institutional Analysis

Abstract: Background Hepatocellular carcinoma (HCC) primarily affects patients with a cirrhotic liver. Reports on the characteristics of patients with HCC in noncirrhotic liver, as well as predictors of recurrence and survival, are scarce. Methods Between 1992 and 2011, 334 patients treated for HCC in noncirrhotic liver were identified from three major hepatobiliary centers. Clinicopathological characteristics were analyzed and independent predictors of recurrence and overall survival were identified using Cox proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 34 publications
5
65
2
1
Order By: Relevance
“…[18][19][20][21] Consistent with the previous studies, our univariate analysis also demonstrated that predictors influencing DFS of HCC with SC were largely tumor-related (Table 3). However, in the multivariate analysis, only macrovascular invasion, lymph node metastasis, satellite nodules, and R1/R2 resection were independent risk factors influencing DFS (Table 3).…”
Section: Discussionsupporting
confidence: 87%
“…[18][19][20][21] Consistent with the previous studies, our univariate analysis also demonstrated that predictors influencing DFS of HCC with SC were largely tumor-related (Table 3). However, in the multivariate analysis, only macrovascular invasion, lymph node metastasis, satellite nodules, and R1/R2 resection were independent risk factors influencing DFS (Table 3).…”
Section: Discussionsupporting
confidence: 87%
“…In general, similar to previous studies, patients had surveillance imaging every 3-4 months for the first 1-3 years and every 6 months from 3 to 5 years. [22][23][24] Information regarding the location and number of lesions, as well as the disease-free interval from the date of initial operation to the development of recurrent disease was recorded. For the cohort of patients who developed repeat recurrences, data on the pattern and time interval between subsequent recurrences also were noted.…”
Section: Patient Demographic and Clinical Datamentioning
confidence: 99%
“…Surgical resection remains the most effective curative treatment for HCC (2), but the high incidence of tumor recurrence makes long-term survival following resection unsatisfactory (3,4). Reducing postoperative recurrence is one of the most significant challenges to improving the prognosis of patients with HCC (5).…”
Section: Introductionmentioning
confidence: 99%